A Qualitative Inquiry on Information Search Behaviour for Services In India - Malik, Anuradha; Dangi, Hamendra K. (Indian Journal of Marketing, 2021)
The service sector is the strongest pillar of any economy and offers tremendous opportunities for research. Information search behaviour for services has been a relatively underexplored area of research, particularly in emerging economies like India. The present study investigated the information search behaviour of consumers for search, experience, and credence services. The study was qualitative in nature and used interviewing and focus group discussion method to probe search behaviour. Data were collected in the Delhi–NCR region in India during the year 2019. Thematic analysis using constant comparison method was performed on the data. The study revealed that consumers exhibited different search behaviour for different types of services. Least efforts were expended for services rich in search attributes. Internet emerged as a popular source of information search for all the services. Age had a substantial impact on search behaviour. Quality of information was a major concern among consumers. This study contributes in broadening the understanding of information search behaviour of consumers of developing economies.